Ökad användning av biodrivmedel i vägtransportsektorn - Lindqvist, Karl-Anders (2008)
The Swedish road transport sector relies almost completely on fossil fuels. In 2007, as much as 96 percent of the total sales of fuels was made up of petrol and diesel, while at the same time the share of total emissions of greenhouse gases in Sweden that came from road transports amounted to close to 30 per cent. Sweden is by no means worse off than any other European country in these respects. In order to address the questions of high oil dependence and CO2 emissions the European Commission has proposed a reinforcement of the legislative framework, with a 10 percent minimum for the market share of biofuels in 2020. Furthermore, the proposed target is binding for the member states, unlike the current voluntary target of 5.75 percent by 2010.